2015
DOI: 10.1590/s0080-623420150000100020
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Enteral Nutritional Therapy in the Healing Process of Pressure Ulcers: A Systematic Review

Abstract: Efetividade da terapia nutricional enteral no processo de cicatrização das úlceras por pressão: revisão sistemática Efectividad de la terapia de nutrición enteral en el proceso de cicatrización de las úlceras por presión: revisión sistemática ABSTRACT Objective: To evaluate the effectiveness of enteral nutritional therapy (ENT) in the healing process of pressure ulcers (PU) in adults and the elderly. Method: A systematic review whose studies were identified through the databases of Cochrane, MEDLINE/ PubMed, S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0
8

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 17 publications
0
3
0
8
Order By: Relevance
“…The preferential access for providing nutritional support to critically ill patients who are unable to ingest food spontaneously, and therefore are at risk of malnutrition, is the enteral route. In this way, the patient can be provided with the necessary calories, proteins, amino acids, vitamins and water, maintaining an adequate nutritional status (22) . A longitudinal study conducted among 471 hospitalized adults identified a higher incidence of PI among those who received enteral nutrition, and also among patients with malnutrition (23) .…”
Section: Contributions To the Area Of Nursing And Healthmentioning
confidence: 99%
“…The preferential access for providing nutritional support to critically ill patients who are unable to ingest food spontaneously, and therefore are at risk of malnutrition, is the enteral route. In this way, the patient can be provided with the necessary calories, proteins, amino acids, vitamins and water, maintaining an adequate nutritional status (22) . A longitudinal study conducted among 471 hospitalized adults identified a higher incidence of PI among those who received enteral nutrition, and also among patients with malnutrition (23) .…”
Section: Contributions To the Area Of Nursing And Healthmentioning
confidence: 99%
“…Nos Estados Unidos, uma investigação com enfermeiros da zona urbana e rural de Montana utilizou a versão preliminar do teste de conhecimento de Pieper, e a porcentagem média de acertos obtida no teste foi de 78% (11)(12) . Já pesquisa realizada na Espanha, utilizando questionário baseado em diretrizes nacionais, com 37 questões, também avaliou o nível de conhecimento dos enfermeiros e técnicos sobre prevenção das úlceras.…”
Section: Discussionunclassified
“…Neste processo a influência pode ser ainda maior, já que é considerado um evento complexo, envolvendo inúmeros estágios interdependentes que se completam com a finalidade da reparação tecidual, caracterizando-se por um processo com aspectos macroscópicos e histológicos, resultantes de uma sequência de eventos celulares ativados e controlados por mediadores químicos (1)(2)(3)(4)(5) . As deficiências calórico-proteicas interferem e dificultam a cicatrização por diversos fatores, dentre eles, destacam-se a depressão do sistema imune, a redução da síntese de colágeno, a inibição da contração da ferida e a redução da proliferação de fibroblastos, culminando na diminuição da qualidade e na…”
Section: Introductionunclassified
“…Neste processo a influência pode ser ainda maior, já que é considerado um evento complexo, envolvendo inúmeros estágios interdependentes que se completam com a finalidade da reparação tecidual, caracterizando-se por um processo com aspectos macroscópicos e histológicos, resultantes de uma sequência de eventos celulares ativados e controlados por mediadores químicos (1)(2)(3)(4)(5) .…”
Section: Introductionunclassified
See 1 more Smart Citation